Association of dietary intake with cancer of the digestive system: a cross-sectional study - Qin, Xinxin; Ge, Litao; Wu, Song; Li, Wei (Frontiers in Nutrition, 2025)
BackgroundIn recent years, the incidence of cancers of the digestive system has been increasing, posing a severe threat to the lives and health of people around the world, and has become one of the leading causes of cancer deaths worldwide. The three most common cancers of the digestive system include gastric, colorectal, and liver cancers, and attention has been paid to the role of diet in the progression of these cancers. However, the relationship between dietary factors and cancers of the digestive system remains to be investigated.MethodsThis study included 30,789 adults aged 20 years or older from the National Health and Nutrition Examination Survey (NHANES), conducted from 2007 to 2018. It assessed the association between 30 dietary factors and digestive system cancers. Descriptive analysis was used to explore the demographic characteristics of the participants and p-values were calculated using a weighted linear regression model. Categorical variables were described as percentages, and p-values were calculated using weighted chi-square tests.ResultsWe found that protein, vitamin B1, calcium, and iron intake were positively associated with colorectal cancer; vitamin B2 and phosphorus intake were negatively related to colorectal cancer; dietary folate and vitamin B12 intake were negatively associated with gastric cancer; vitamin D and copper intake were positively associated with gastric cancer; vitamin E intake was negatively related to the development of hepatocellular carcinoma; and lycopene, vitamin B2, calcium, iron, and zinc intake was positively associated with the development of liver cancer. Other than that, we did not observe any correlation between other dietary factors and cancers of the digestive system.ConclusionDietary intake is associated with digestive system cancers, and more epidemiologic studies are needed to validate our results.